Neuropsychiatric disorders among Ecuadorian patients with multiple sclerosis and neuromyelitis optica spectrum disorder - Edgar Patricio Correa-Díaz; Edgar Patricio Correa-Díaz; Ruth Jimbo Sotomayor; Ruth Jimbo Sotomayor; Jorge Rubén Pilco Romero; Patricio Alexander Merino Aguilera; Patricio Alexander Merino Aguilera (Frontiers in Neurology, 2025)
IntroductionMultiple Sclerosis (MS) and Neuromyelitis Optica Spectrum Disorder (NMOSD) are chronic demyelinating diseases of the central nervous system, there is an association between these diseases and neuropsychiatric disorders, which directly impacts the course of the disease and the quality of life of the patients.ObjectiveTo determine the prevalence of psychiatric disorders in patients with MS and NMOSD and its relationship with age and disability. Materials and methods: It is a cross-sectional study, 151 patients were included, 117 patients with MS and 34 patients with NMOSD. Information was obtained by collecting data from records of the patients. In order to establish the diagnoses of anxiety and depression, the Hamilton Depression Rating Scale (HDRS) and the Beck Depression Inventory (BDI) scales were completed.ResultsMS and NMOSD were frequent in female sex and mestizo ethnicity. The psychiatric disorders were frequent in both diseases (70.9% in MS and 85% in NMOSD), the most frequent pathologies were anxiety and depression. We found low frequency of attempted suicide. Anxiety and depression were present in patients between 41 and 50 years of age. There is not a correlation between the severity of anxiety and depression with age and disability.ConclusionIt is the first Ecuadorian study in which we established a high prevalence of anxiety and depression in MS and NMOSD patients, the severity of both disease was not related with age and disability.